Chitooligosaccharide supplementation in low-fish meal diets for Pacific white shrimp (Litopenaeus vannamei): Effects on growth, innate immunity, gut histology, and immune-related genes expression. Issue 80 (September 2018) - Rahimnejad, Samad; Yuan, Xiangli; Wang, Ling; Lu, Kangle; Song, Kai; Zhang, Chunxiao
Abstract: This study evaluated the effects of supplementing chitooligosaccharide (COS) in low fish meal (FM) diets on growth, immune response, intestine and hepatopancrease histology, and expression of inflammatory and immune-related genes in Pacific white shrimp ( Litopenaeus vannamei ). A basal diet was formulated using FM and soybean meal (SM) as primary protein sources and considered as a high FM (HFM) diet, then a low FM (LFM) diet was prepared by substituting 50% of FM with SM and supplemented with 0, 0.3, 0.6, 0.9, 1.2 or 1.5 g COS kg −1 diet (LFM, COS3, COS6, COS9, COS12 and COS15 diets). Each diet was fed to quadruplicate groups of shrimp (0.9 g) to apparent satiation three times daily for eight weeks. At the end of the experiment no significant changes in growth and survival rate were observed among treatments ( P  > 0.05). FM replacement led to significant ( P  < 0.05) reduction of serum lysozyme activity and significant improvements were obtained by adding 0.3 or 0.6 g kg −1 COS to the LFM diet. A significant decrease in nitric oxide synthase activity was found in LFM group and no beneficial effects could be achieved by COS application. LFM group showed higher hepatopancrease superoxide dismutase and glutathione peroxidase activities than HFM group and further enhancements were obtained by COS application. Hepatopancrease total antioxidant capacity and alkaline phosphatase activity decreased in LFM group and COS supplementation improved their values. Expression of lysozyme, crustin, Pen3 and proPo genes were significantly up-regulated in hepatopancrease of groups received 0.3–0.9 g COS kg −1 diet. FM substitution enhanced the expression of HSP70 and inflammatory genes such as AIF and TNF in hepatopancrease and intestine, and COS administration at a moderate level down-regulated their expression level. Remarkable enhancement in intestinal fold height was obtained by inclusion of 0.3 or 0.6 g COS kg −1 diet compared to the group received LFM diet. Shrimps fed HFM and COS containing diets exhibited higher number of E-cells within their hepatopancrease tubules than the LFM group. The findings in this study clearly demonstrated that COS could enhance non-specific immune response and antioxidant activity, and ameliorate the negative impacts of high SM diets on gut and hepatopancrease health in pacific white shrimp. The optimum inclusion level of COS seems to be 0.3–0.6 g kg −1 of diet. Highlights: Chitooligosaccharide (COS) inclusion was evaluated in low-fish meal diets for shrimp. Non-specific immune response of shrimp was augmented by COS application. COS supplementation enhanced the antioxidant enzymes activity in hepatopancrease. Expression of immune related genes was up-regulated by COS addition. COS beneficially affected the gut and hepatopancrease health.